The girls' book : how to be the best at everything - Foster, Juliana; Enright, Amanda; Wingate, Philippa (New York : Scholastic, 2007)
A book of activities for girls that provides step-by-step instructions for everything from strumming a guitar, eating with chopsticks, and making a camp in the wilderness to coping when zombies attack and surviving an alien invasion.
First published in Great Britain in 2007 by Buster Books.
School Library Journal, September 2007.
Horn Book, April 2008.
Kirkus Review, August 2007.
School Library Journal.
Horn Book.
Keywords: Girls -- Life skills guides -- Juvenile literature; Handicraft for girls -- Juvenile literature; Amusements -- Juvenile literature; Life skills; Handicraft; Amusements; Life skills; Handicraft; Amusements; Recreation; Amusements